Display system of adjustable LIBRAS window for educational contents on the Web and Brazilian Digital TV - Dos Santos, Edson Benedito [UNESP]; De Oliveira, Hilda Carvalho [UNESP]; Oliveira, Celso Socorro [UNESP] (My University, 2011)
This paper presents a proposal to contribute to the growing demand in learning Brazilian Sign Language (LIBRAS). The proposal focus is providing flexibility of building the content for teaching-learning of LIBRAS through subtitled videos and windows with LIBRAS interpreters. Contents can be prepared in accordance with the need and suitability for in-class, without requiring Informatics specialists. This content is automatically converted to be viewed in Web environments and in environments that use the standard Ginga-NCL, such as IPTV and Open Digital TV (ODTV) in Brazil. The window with the recording of the LIBRAS interpreter (LIBRAS window) is controlled by the user and can be hidden or adjusted in size and position. The work was guided by the law and Brazilian Technical Standards. In this context, this paper has as main objective to present the control system and display of the LIBRAS window for environments Web, IPTV and Brazilian ODTV.
Keywords: Accessibility; Deaf; Digital TV; E-learning; Ginga; LIBRAS